2015
DOI: 10.1371/journal.pone.0145372
|View full text |Cite
|
Sign up to set email alerts
|

Multi-Morbidity in Hospitalised Older Patients: Who Are the Complex Elderly?

Abstract: BackgroundNo formal definition for the “complex elderly” exists; moreover, these older patients with high levels of multi-morbidity are not readily identified as such at point of hospitalisation, thus missing a valuable opportunity to manage the older patient appropriately within the hospital setting.ObjectivesTo empirically identify the complex elderly patient based on degree of multi-morbidity.DesignRetrospective observational study using administrative data.SettingEnglish hospitals during the financial year… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
44
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(48 citation statements)
references
References 23 publications
3
44
1
Order By: Relevance
“…This finding is not consistent with previous reports in primary care populations, where multimorbidity is generally more common in females [6,12,24]. Studies reporting the prevalence of multimorbidity by gender in hospitalised populations are limited, and report conflicting results [14,16,47,48]. We also noted some evidence of a different pattern of multimorbidity between males and females at different age groups.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…This finding is not consistent with previous reports in primary care populations, where multimorbidity is generally more common in females [6,12,24]. Studies reporting the prevalence of multimorbidity by gender in hospitalised populations are limited, and report conflicting results [14,16,47,48]. We also noted some evidence of a different pattern of multimorbidity between males and females at different age groups.…”
Section: Discussioncontrasting
confidence: 99%
“…The prevalence of multimorbidity in hospitalised patients varies widely among studies (22% to 99.7%) [12][13][14][15][16][17]. Some of this difference is likely to be due to different methods used for measuring multimorbidity including how multimorbidity is defined, the number and type of conditions included, data sources and coding schemes, population studied, and setting [18].…”
Section: Introductionmentioning
confidence: 99%
“…Finally, a significant factor impacting acute hospitals is the changing nature of the patients cared for in them: patients are older, frailer and have more complex conditions than in previous decades [15]. This shift to older, frailer patients in acute hospitals, changes the way a hospital delivers care and the skills mix needed within the hospital to deliver high quality care that ensures patients can be safely treated and discharged.…”
Section: The Problem Of 'Lack Of Integration'mentioning
confidence: 99%
“…Our literature search for studies reporting the prevalence of multimorbidity in hospitalized patients revealed that the majority of studies have been focussed on adults over 65 years and/or patients with high severity of illness or highly selected patients. [21][22][23][24][25][26][27][28][29][30] Studies including unselected younger patients have reported the overall prevalence of multimorbidity, [31][32][33][34] but less often in detail by gender or specific age groups, 32,33 and we did not identify any studies investigating the prevalence of multimorbidity by urban-rural area or SES. In Scotland, rurality and SES are taken into account for allocating resources to NHS Boards.…”
Section: Introductionmentioning
confidence: 99%